Geometry of design studies in proportion and composition - Elam, Kimberly 1951- (Design briefs, 2011)
"Geometry of design, second edition, with its detailed diagrams and beautiful vellum overlays, explains not only how the science of measurement informs, even creates, beauty in nature and art but, more importantly, how we can use these techniques to create beauty in our own designs. The new edition features an additional thirty-six pages of content that offers more visual explanations of these geometric principles of work." -- Provided by publisher